Diagnostic and Interventional Imaging in Various Diseases - Romica Cergan; Mihai Dumitru; Adrian Costache (Medicina, 2024)
Diagnostic and interventional imaging is a cornerstone in the management of cases in various medical and surgical domains, such as neonatology, neurology, neurosurgery, otorhinolaryngology, dentistry, gynecology and urology [...]